2008
DOI: 10.1007/s00417-008-1025-y
|View full text |Cite
|
Sign up to set email alerts
|

Peeling of internal limiting membrane during vitrectomy for complicated retinal detachment prevents epimacular membrane formation

Abstract: ILM peeling at the macula during vitreous surgery with silicone oil for the treatment of complicated retinal detachment may prevent epimacular membrane formation without negatively affecting distant visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 10 publications
5
42
0
6
Order By: Relevance
“…30,31 Case analyses of vitrectomy itself with ILM peeling in eyes with retinal detachment have been mentioned during numerous ophthalmic congresses.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Case analyses of vitrectomy itself with ILM peeling in eyes with retinal detachment have been mentioned during numerous ophthalmic congresses.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Odrobina et al found ERM in 17% of patients in whom the ILM peeling had not been performed, whereas no ERM case was identified in the group with ILM peeling [18]. Kiss et al found that ERM develops in 20.5% of patients with complicated retinal detachment, treated with vitrectomy with silicone oil tamponade [5]. We did not find a relationship between the degree of PVR and visual acuity, probably due to the fact that in the studied groups PVR was never greater than stage C1.…”
Section: Discussionmentioning
confidence: 96%
“…In turn, in 1993 Wendel et al suggested a modification of ILM removal in the treatment of idiopathic macular hole (MH) [2]. ILM peeling is particularly recommended during vitrectomy performed due to macular hole, diabetic macular edema, retinal vein thrombosis, or primary ERM as well as in some forms of retinal detachment [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, ILM peeling may play a role in the surgical repair of retinal detachment as it can prevent ERM formation without negatively affecting distant visual acuity. In a study comparing 20 eyes with ILM peeling and 22 eyes without ILM peeling after complicated retinal detachment surgery with silicone oil, Aras et al 67 showed improved visual acuity in the ILM peeling group and 0% postoperative ERM formation compared with 27% in the non-ILM peeling group. By inhibiting later ERM formation, initial ILM peeling in retinal detachment surgery can mean improved visual acuity and a reduced number of surgeries.…”
Section: Epiretinal Membranementioning
confidence: 97%